Pembinaan kelompok petani budidaya melalui kegiatan aplikasi teknik probiotik dan pembuatan pakan berbasis bahan lokal pada budidaya ikan lele di Desa Koto Pangean Kecamatan Pangean Kabupaten Kuantan Singingi - Usman M Tang; Niken Ayu Pamukas; Adelina Adelina; Iesje Lukistyowati; Mulyadi Mulyadi (Unri Conference Series: Community Engagement, 2019)
Koto Pangean village has an area of 15 ha, the topography of the area is flat and hilly land with a high of 300 m up to from marine water surface. Type of soil type is black on the top layer and yellow on the bottom layer. Width of the waters of Koto Pangean Village is 2,003.25 ha, has been used for fisheries activities ranging from 2.50 ha in lakes, 1.8 ha swamps, rivers of 180 ha and 10 ha for a fishpond. Several kinds of fish are reared in this village such as African catfish (Clarias batrachus), tilapia (Oreochromis niloticus) and carp (Cyprinus carpio). The main problems faced by fish farmers in this village are: the occurrence of fish deaths caused by decreasing of water quality, accumulation of organic matter, the number of fish attacked by disease and increasing number of pathogenic microorganisms that attack fish, and high commercial fishmeal prices which results in high operational costs for fish farming. To overcome these problems, knowledge innovations are carried out to farmer groups by conducting counselling about; 1. the use of probiotics to improve the soil quality and pond water, 2. Method to prevent fish from disease attacks, 3. how to make pellets by utilizing local ingredients of good quality. The results of the activities that have been carried out show that there is an increase in knowledge and skills of fish farmers, especially being able to increase catfish production with probiotic technology and decreasing operational costs for providing fish meal as a result of the increasing the income and welfare of fish farmer groups.